The Effect of Co2-Brine-Rock Interaction Towards Sand Onset Modeling in Dolomite-Rich Sandstone: A Case Study in Air Benakat Formation, South Sumatera, Indonesia - Prasandi Abdul Aziz; Bagus Endar Bachtiar Nurhandoko; Taufan Marhaendrajana; Utjok W.R. Siagian; Tutuka Ariadji (Scientific Contributions Oil and Gas, 2024)
Carbon Capture Utilization Storage (CCUS) into geological storage (e.g., Enhanced Oil or Gas Recovery) provides a solution to reduce CO2 emissions yet remains a potential operational problem, such as sand problem phenomena in producer well. This study performs several experimental works (i.e., time-lapse dry mass measurements, , X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM) and elastic wave measurements) by using CO2-brine-rock batch experimental setup to observe mineral dissolution, pore structures alteration as well as rock physics alteration due to CO2-brine-rock interactions.This study used an outcrop sample of dolomite-rich sandstone from Air Benakat formation, South Sumatera, Indonesia. Our experimental works observed dolomite dissolution, secondary porosity development as well as rock strength reduction indirectly due to CO2-brine-rock interactions. The results of elastic wave velocity measurements (i.e. P & S waves) were then used to modify a considerable sand onset prediction model. Thus, the modified model demonstrates that considering CO2-brine-rock interactions could help to design better sand management strategy in producer well.